ANALYSIS OF TELEVISION SIGNAL BOOSTERS USING DIGITAL TELEVISION BOOSTERS AND ANTENNA - Putri, Venny Manca; Imansyah, Fitri; Yacoub, Redi Ratiandi (Faculty of Engineering, Universitas Tanjungpura, 2024)
A digital antenna is a device used to capture digital signals. Digital television broadcasts are capable of transmitting better reception quality image signals on the television screen than analog broadcasts. Using an antenna without a booster causes less than optimal reception for several stations that are quite far from the receiving antenna. The television antenna booster functions as an amplifier for signal losses received from the antenna via coaxial cable. The signal that enters the antenna through the cable is a very weak RF signal. The booster itself works as an RF signal amplifier and also acts as a frequency selector used by the television receiver (VHF or UHF). This research aims to analyze the comparison of the performance of two antenna boosters, namely the TOYOSAKI Booster and MATRIX Booster, using digital antennas, namely the TOYOSAKI, MATTRIX and TAFFWARE antennas, to find a comparison of which antenna and booster are the best. This research uses the SINPO method, namely a number code to assess signal strength, interference, atmospheric noise, propagation conditions, and general impression of reception. Ratings are made with numbers ranging from 5 (very good) to 1 (very bad). The research results show that the quality of the images produced by the TOYOSAKI and MATRIX antennas is better using the MATRIX Booster than using the TOYOSAKI Booster. Meanwhile, for the TAFFWARE antenna, it is better to use a TOYOSAKI Booster than to use a MATRIX.